Devotions and desires : histories of sexuality and religion in the twentieth-century United States - Frank, Gillian; Moreton, Bethany; White, Heather Rachelle, 1974- (The University of North Carolina Press, 2018)
At a moment when 'freedom of religion' rhetoric fuels public debate, it is easy to assume that sex and religion have faced each other in pitched battle throughout modern U.S. history. Yet, by tracking the nation's changing religious and sexual landscapes over the twentieth century, this text challenges that zero-sum account of sexuality locked in a struggle with religion. It shows that religion played a central role in the history of sexuality in the United States, shaping sexual politics, communities, and identities.